THE OPTION ON ELECTRIC ENERGY FOR THE DECREASE OF RISK ON THE EXAMPLE OF EEX (EUROPEAN ENERGY EXCHANGE) - Latas, Tatjana; Jeremić, Zoran (The European Journal of Applied Economics, 2017)
Electricity market deregulation and liberalization have led to high volatility on power exchanges, which require the use of derivatives in energy markets for more efficient risk management which the participants at the market are exposed to. The available options are one of the derivatives that have entered liquid markets. Therefore, this paper presents an example from the most developed energy exchange EEX (European Energy Exchange), with the aim of applying verified scientific methods to check the practice of functioning of liquid energy market,by using options to reduce the risk. The most frequently used models for hedging future open positions and evaluation of premium on options in practice are the Black - Scholes and Black 76 model, which are therefore presented in the text. South East European Power Exchange (SEEPEX) has started operating in Serbia. Its development is going to be via integration with regional markets in the direction of integrationof the total electric energy market in Europe. That path will be long, but it has already required the knowledge of market instruments used intrading and risk management at the power exchanges. Presented results refer to the essential knowledge of dynamic variables that options bring into the energy market in order to reduce the risk.
Keywords: electric energy exchange; derivatives; options